Glomerular endothelial cell fenestrations: an integral component of the glomerular filtration barrier - Satchell, Simon C; Braet, Filip (American journal of physiology. Renal physiology, 2009)
Glomerular endothelial cell (GEnC) fenestrations are analogous to podocyte filtration slits, but their important contribution to the glomerular filtration barrier has not received corresponding attention. GEnC fenestrations are transcytoplasmic holes, specialized for their unique role as a prerequisite for filtration across the glomerular capillary wall. Glomerular filtration rate is dependent on the fractional area of the fenestrations and, through the glycocalyx they contain, GEnC fenestrations are important in restriction of protein passage. Hence, dysregulation of GEnC fenestrations may be associated with both renal failure and proteinuria, and the pathophysiological importance of GEnC fenestrations is well characterized in conditions such as preeclampsia. Recent evidence suggests a wider significance in repair of glomerular injury and in common, yet serious, conditions, including diabetic nephropathy. Study of endothelial cell fenestrations is challenging because of limited availability of suitable in vitro models and by the requirement for electron microscopy to image these sub-100-nm structures. However, extensive evidence, from glomerular development in rodents to in vitro studies in human GEnC, points to vascular endothelial growth factor (VEGF) as a key inducer of fenestrations. In systemic endothelial fenestrations, the intracellular pathways through which VEGF acts to induce fenestrations include a key role for the fenestral diaphragm protein plasmalemmal vesicle-associated protein-1 (PV-1). The role of PV-1 in GEnC is less clear, not least because of controversy over existence of GEnC fenestral diaphragms. In this article, the structure-function relationships of GEnC fenestrations will be evaluated in depth, their role in health and disease explored, and the outlook for future study and therapeutic implications of these peculiar structures will be approached.